Establishment of an in vivo simulating co‐culture assay platform for genotoxicity of multi‐walled carbon nanotubes. Issue 4 (1st April 2018) - Fukai, Emi; Sato, Haruna; Watanabe, Masatoshi; Nakae, Dai; Totsuka, Yukari
Abstract : Engineered nanomaterials (ENM) are now used in a wide variety of fields, and, thus, their safety should urgently be assessed and secured. It has been suggested that inflammatory responses via the phagocytosis of ENM by macrophages is a key mechanism for their genotoxicity. The present study was conducted to establish a mechanism‐based assay to evaluate the genotoxicity of ENM under conditions simulating an in vivo situation, featuring a co‐culture system of murine lung resident cells (GDL1) and immune cells (RAW264.7). GDL1 were cultured with or without RAW264.7, exposed to a multi‐walled carbon nanotube (MWCNT), and then analyzed for mutagenicity and underlying mechanisms. Mutation frequencies induced in GDL1 by the MWCNT were significantly greater with the co‐existence of RAW264.7 than in its absence. Mutation spectra observed in GDL1 co‐cultured with RAW264.7 were different from those seen in GDL1 cultured alone, but similar to those observed in the lungs of mice exposed to the MWCNT in vivo. Inflammatory cytokines, such as IL‐1β and TNF‐α, were produced from RAW264.7 cells treated with the MWCNT. The generation of reactive oxygen species and the formation of 8‐oxodeoxyguanosine in GDL1 exposed to the MWCNT were greater in the co‐culture conditions than in the single culture conditions. Based on these findings, it is indicated that inflammatory responses are involved in the genotoxicity of MWCNT, and that the presently established, novel in vitro assay featuring a co‐culture system of tissue resident cells with immune cells is suitable to evaluate the genotoxicity of ENM. Abstract : We conducted a mechanism‐based assay to evaluate the genotoxicity of engineered nanomaterials under conditions mimicking an in vivo situation, featuring a co‐culture system of murine lung resident cells (GDL1) and immune cells (RAW264.7).Mutation frequencies induced in GDL1 by the MWCNT were significantly greater with the co‐existence of RAW264.7. Moreover, mutation spectra observed in GDL1 co‐cultured with RAW264.7 were similar to those observed in the lungs of mice exposed to the MWCNT in vivo.